Motivation for public service, organizational commitment, and employee performance: A study of civil servants in the Ministry of Home Affairs in Vietnam - Phuong Huu Tung (International Journal of Computer Information Systems and Industrial Management Applications, 2026)
Public service motivation is considered a crucial resource driving the behavior and performance of public sector employees, but the mechanisms for transforming this motivation into work performance remain unclear in the Vietnamese context. This study examines the relationship between Public Service Motivation (PSM), organizational commitment, and work performance, and considers the mediating role of commitment among civil servants in the Ministry of Home Affairs in Vietnam. Data comprising 326 observations were collected using a 5-point Likert scale and analyzed through Cronbach's Alpha, exploratory factor analysis, regression, and bootstrap with 5,000 replicates. The results show that PSM positively impacts organizational commitment and employee work performance. Organizational commitment also positively influences employee work performance. The research implies that public human resource management needs to simultaneously reinforce the value of public service, build a supportive work environment, and enhance engagement to transform motivation for service into effective public performance.